Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1111/medu.13358
|View full text |Cite
|
Sign up to set email alerts
|

Care of the dying: a qualitative exploration of Foundation Year doctors’ experiences

Abstract: Areas for improvement were identified around all five main themes. These will be useful for informing those involved in undergraduate and foundation training on how to improve the experiences of Foundation Year doctors and thereby improve patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 16 publications
(52 reference statements)
1
22
0
Order By: Relevance
“…5,6,7,9 The limitations of providing palliative care in hospital settings, with dying patients being missed on ward rounds and given aggressive treatments have also been previously reported. 5,13 All participants felt that their hospice placement had or would change their practice, mainly through acquisition of transferable skills such as communication skills, improved recognition of dying and management of symptoms, findings in keeping with previous research. 17 Only one participant believed that palliative care skills were not required in his current specialty (general surgery -in which other studies have shown palliative care can be sub-optimal).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…5,6,7,9 The limitations of providing palliative care in hospital settings, with dying patients being missed on ward rounds and given aggressive treatments have also been previously reported. 5,13 All participants felt that their hospice placement had or would change their practice, mainly through acquisition of transferable skills such as communication skills, improved recognition of dying and management of symptoms, findings in keeping with previous research. 17 Only one participant believed that palliative care skills were not required in his current specialty (general surgery -in which other studies have shown palliative care can be sub-optimal).…”
Section: Discussionsupporting
confidence: 76%
“…For example, communication skills have been acknowledged as a predominant learning need for junior doctors along with recognition and symptom control of dying patients. 13 Gaps in education and experience in both communication skills and palliative care have also been recognised previously, and other study participants have described being afraid of talking to dying patients and not knowing how to care for them. 5,6,7,9 The limitations of providing palliative care in hospital settings, with dying patients being missed on ward rounds and given aggressive treatments have also been previously reported.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Palliative care requires a patient-centered holistic approach encompassing biomedical competence and compassionate caring. The domain of palliative care can be emotionally evocative and a cultural shift away from the disease-based, curative model that may challenge how learners see themselves as emerging practitioners [7,[17][18][19][20][21][22][23][24][25][26]. In most published literature on palliative care education, learning is considered as individualistic, following the acquisition metaphor.…”
Section: Creating Conditions To Support Learning and Identity Developmentioning
confidence: 99%
“…We found that FYs' experiences are variable and, within the five priorities, 5 good practice and areas for improvement exist. 6 In this paper we present the primary data analysis related to question three.…”
Section: Introductionmentioning
confidence: 99%